Persistence of humoral immune response to SARS-CoV-2 up to 7 months post-infection: Cross-sectional study, South India, 2020–21. Issue 3 (September 2021) - Thangaraj, Jeromie Wesley Vivian; Kumar, Muthusamy Santhosh; Kumar, CP Girish; Kumar, V Saravana; Kumar, Nathella Pavan; Bhatnagar, Tarun; Ponnaiah, Manickam; Sabarinathan, R; Sudharani, D; Nancy, Arul; Jagadeesan, M; Babu, Subash; et al.
Highlights: Few studies are available about persistence of SARS-CoV-2 antibodies from LMICs. Anti-nucleocapsid antibodies waned over a 7 month period post SARS-CoV-2 infection. Anti S1-RBD antibodies were relatively stable. Neutralizing antibodies were persistent up to seven months post-infection.